Kinerja Keuangan Pemerintah Daerah: Ukuran Pemerintah Daerah, Belanja Modal, Belanja Rutin, dan Indeks Reformasi Birokrasi - Budiharjo, Roy; Hariani, Swarmilah; Sagita, Ardio (Gorontalo Accounting Journal, 2025)
This study aims to analyze the influence of local government size, capital expenditure, routine expenditure, and the bureaucratic reform index on the financial performance of local governments in Central Java Province. Secondary data were collected from district and city governments in Central Java Province, with samples selected using a purposive sampling method based on local government financial reports and information on the bureaucratic reform index from 2019-2021. This study employs multiple linear regression analysis with partial testing using the t-statistic, following classical assumption testing. The results indicate that local government size has a significant positive effect on financial performance, while capital and routine expenditures have significant negative effects. Conversely, the bureaucratic reform index has no effect on financial performance. The findings provide insights for local governments in managing finances to improve efficiency and effectiveness in public service delivery.